Cardiac Electrophysiologic Effects of Different Local Anesthetics in Langendorff-Perfused Rabbit Hearts - Julian Wolfes; Amy Katthöfer; Felix Wegner; Benjamin Rath; Florian Doldi; Sati Güler-Eren; Lars Eckardt; Gerrit Frommeyer; Christian Ellermann (Cardiovascular Toxicology, 2026)

Electrophysiological Profile of Different Antiviral Therapies in a Rabbit Whole-Heart Model - Julian Wolfes; Lina Kirchner; Florian Doldi; Felix Wegner; Benjamin Rath; Lars Eckardt; Christian Ellermann; Gerrit Frommeyer (Cardiovascular Toxicology, 2024)
Antiviral therapies for treatment of COVID-19 may be associated with significant proarrhythmic potential. In the present study, the potential cardiotoxic side effects of these therapies were evaluated using a Langendorff model of the isolated rabbit heart. 51 hearts of female rabbits were retrogradely perfused, employing a Langendorff-setup. Eight catheters were placed endo- and epicardially to perform an electrophysiology study, thus obtaining cycle length-dependent action potential duration at 90% of repolarization (APD 90 ), QT intervals and dispersion of repolarization. After generating baseline data, the hearts were assigned to four groups: In group 1 (HXC), hearts were treated with 1 µM hydroxychloroquine. Thereafter, 3 µM hydroxychloroquine were infused additionally. Group 2 (HXC + AZI) was perfused with 3 µM hydroxychloroquine followed by 150 µM azithromycin. In group 3 (LOP) the hearts were perfused with 3 µM lopinavir followed by 5 µM and 10 µM lopinavir. Group 4 (REM) was perfused with 1 µM remdesivir followed by 5 µM and 10 µM remdesivir. Hydroxychloroquine- and azithromycin-based therapies have a significant proarrhythmic potential mediated by action potential prolongation and an increase in dispersion. Lopinavir and remdesivir showed overall significantly less pronounced changes in electrophysiology. In accordance with the reported bradycardic events under remdesivir, it significantly reduced the rate of the ventricular escape rhythm.

A single Thaumarchaeon drives nitrification in deep oligotrophic Lake Constance - Janina Herber; Franziska Klotz; Benjamin Frommeyer; Severin Weis; Dietmar Straile; Allison Kolar; Johannes Sikorski; Markus Egert; Michael Dannenmann; Michael Pester (Environmental Microbiology, 2020)
Summary Ammonia released during organic matter mineralization is converted during nitrification to nitrate. We followed spatiotemporal dynamics of the nitrifying microbial community in deep oligotrophic Lake Constance. Depth‐dependent decrease of total ammonium (0.01–0.84 μM) indicated the hypolimnion as the major place of nitrification with 15 N‐isotope dilution measurements indicating a threefold daily turnover of hypolimnetic total ammonium. This was mirrored by a strong increase of ammonia‐oxidizing Thaumarchaeota towards the hypolimnion (13%–21% of bacterioplankton) throughout spring to autumn as revealed by amplicon sequencing and quantitative polymerase chain reaction. Ammonia‐oxidizing bacteria were typically two orders of magnitude less abundant and completely ammonia‐oxidizing (comammox) bacteria were not detected. Both, 16S rRNA gene and amoA (encoding ammonia monooxygenase subunit B) analyses identified only one major species‐level operational taxonomic unit (OTU) of Thaumarchaeota (99% of all ammonia oxidizers in the hypolimnion), which was affiliated to Nitrosopumilus spp. The relative abundance distribution of the single Thaumarchaeon strongly correlated to an equally abundant Chloroflexi clade CL500‐11 OTU and a Nitrospira OTU that was one order of magnitude less abundant. The latter dominated among recognized nitrite oxidizers. This extremely low diversity of nitrifiers shows how vulnerable the ecosystem process of nitrification may be in Lake Constance as Central Europe's third largest lake.